El delito de acoso o stalking en españa (2020)
The Organic Law 1/2015, of March 30, introduced the crime of harassment or stalking in article 172 ter CP, thinking mainly of women who suffer acts of harassment by their former partners. The legislator followed the model of the crime of persecution (Nachstellung) of § 238 StGB, although this precept has been recently reformed, ceasing to be a crime of result to become a crime of suitability. However, the Spanish regulation has dispensed with the analog clause of the German provision, avoiding the infringement of the principle of legal security. On the other hand, our judicial bodies have interpreted this illicit act in an excessively flexible way, punishing behaviors that generate mere anxiety, violating the principle of minimal intervention.